Methods and Applications for Amplified Bursts of Picosecond-Spaced Ultrashort Pulses - Stummer Vinzenz; Kaksis Edgar; Flöry Tobias; Schneller Matthias; Zeiler Markus; Hu Hongtao; Pugžlys Audrius; Baltuška Andrius (EPJ Web of Conferences)
Generating packages of picosecond-spaced ultrashort pulses yields various advantages in their application in nonlinear spectroscopy, micromachining, and plasma generation. We outline methods of burst amplification, with a focus on recent advancements in the generation and application of amplified pulse bursts.